The peace dividend - Gleditsch, Nils Petter, 1942- (Amsterdam ; New York : Elsevier, 1996)
The papers collected in this volume demonstrate how different kinds of analytical approach can be used to anticipate the economic repercussions of systematic reduction of military spending. This volume will be of interest to economists; scholars in peace studies, international relations and such like; and officials of national governments and international bodies dealing with disarmament issues and with economic restructuring.
The peace dividend : myth or reality? / Michael D. Intriligator -- The macroeconomics of the peace dividend in the U.K. / Ron P. Smith -- The peace dividend in France / Raymond Courbis -- Size, determinants and effects of Italian military spending / Stefania Tomasini -- The national peace dividend / Olav Bjerkholt -- The Greek military sector and macroeconomic effects of military spending in Greece / Vassilios Stavrinos -- The peace dividend in Turkey / Suleyman Ozmucur -- Disarmament in the Netherlands : medium-term economic consequences / Michiel Vergeer -- Military spending and the peace dividend in Denmark / Claus Flyng Baunkjaer -- Macroeconomic impacts of disarmament and the peace dividend in the U.S. economy / Bert G. Hickman -- The peace dividend in Norway : domestic or international? / Olav Bjerkholt -- The peace dividend in Costa Rica : historical and counterfactual / Juan-Rafael Vargas -- The peace dividend in South Africa / Mike L. Truu -- A comparison of CGE and econometric approaches to modeling government (military) spending / Innwon Park -- The international peace dividend / Ron P. Smith -- The economics of disarmament in Africa / Jean K. Thisen -- East-Southeast Asian security in context / Jose V. Ciprut -- A peace dividend in South America? : defense conversion in Argentina and Chile / Thomas Scheetz -- towards a peace dividend in the Middle East : the new dynamics of military spending / Michael D. Ward -- Economic effects of military expenditure in developing countries : a survey / J. Paul Dunne -- Military spending cuts and the global economy / Warwick J. McKibbin -- Global disarmament and developing countries : a MULTIMOD simulation / Steven Symansky -- Multilateral disarmament : project LINK simulations / Peter Pauly -- Economic aspects of peacekeeping operations / Kanta Marwah.
Includes bibliographical references (p. [555]-582) and indexes.
Description based on print version record.
Keywords: Disarmament -- Economic aspects -- Case studies; Economic conversion -- Case studies; Peace -- Economic aspects -- Case studies; Defense industries -- Employees -- Supply and demand -- Case studies; Unemployment -- Case studies; Business & Economics -- Industries -- General; Business & Economics -- Econometrics; Political economy; Economic statistics